Effect of Carboxymethyl Konjac Glucomannan on the Gel Properties of Silver Carp Surimi: A Study on the Regulatory Mechanism of Substitution Degree - Wenli Yan; Zhihan Ouyang; Xiaoying Luo; Rankun Xiao; Siqiao Liao; Fatang Jiang; Yonghui Li; Shanbai Xiong; Tao Yin; Xiangwei Zhu (Foods)
Freshwater surimi typically exhibits poor gel-forming capability and is prone to gel deterioration, limiting its applications in food products. This study successfully prepared silver carp surimi gels with improved gel strength and water-holding capacity (WHC) using carboxymethyl konjac glucomannan (CKGM) as a functional modifier. Furthermore, the regulatory mechanism of CKGM with different degrees of substitution (DS) on the gel properties of silver carp surimi was systematically investigated. Results demonstrated that DS significantly influenced gel strength, WHC, and microstructure. CKGM (DS = 0.21%) substantially enhanced the gel strength and WHC through strengthened hydrophobic interactions and hydrogen-bond networks. However, CKGM with a higher DS (0.41%) induced a steric hindrance effect, decreasing elastic modulus and WHC and resulting in a more porous gel network. Raman spectroscopy analysis revealed that CKGM facilitated the conformational transition of myofibrillar proteins from α-helix to β-sheet, thereby improving the density of the gel network. The study provides theoretical foundations and technical guidance for the quality improvement of surimi products.